Pediatric allergy: a common occurrence with multifarious implications - Maya Shinde, Dr.; Shweta Chaudhary, Dr.; Smita Patil, Dr.; Chetana Jagtap, Dr.; Sanket Kunte, Dr.; Alok Patel, Dr. (International Journal of Dental Research, 2022)
Pediatric professionals treat natureâ€™s most benevolent creation i.e., the child.It is important to focus not only on oral health but also on the overall health of the pediatric patient because oral health is an integral part of total development.There are various dental materials ranging from diagnosis to rehabilitation for the management of oral diseases that are not devoid of posing a potential risk of inducing allergic reactions to Pediatric patients in the dental setting.Most importantly, a dental practitioner must be trained in medical emergencies and be capable of resuscitating a patient. Not only the dentist but also the assistants present in the clinic should be trained on how to manage any allergic emergency conditions in children in dental settings.As some of these diseases have higher rates of morbidity and mortality, management of such conditions requires a multidisciplinary medical team approach consisting of physicians, dermatologists, Pediatric dentists, and ophthalmologists.So, this review involves in-detail information regarding what is an allergy, history of allergy, allergic and immunological responses of the oral mucosa, dental materials prone to allergies, its diagnosis, and treatment modalities in child hoping that it will be helpful to every practicing pediatric professional.Â Â